Management of old naso-orbital fractures with ocular involvement and associated complications caused by facial trauma (Medical Journal of Indonesia, 2018)
A 14-years-old boy came with chief complaint of epiphora and history of globe rupture repair surgery due to facial trauma one year ago. Patient got complications from the trauma, including nasolacrimal duct obstruction, phthisis bulbi, enophthalmos, facial deformities, and ptosis. Multidisciplinary approach was performed simultaneously in one session surgery which included oral mucosal graft for non-irritative phthisis bulbi, silicone block implant for blowout fracture, external dacrycystorhinostomy for obstructed nasolacrimal duct, fascia lata brow suspension/frontalis sling for ptosis, and septorhinoplasty for nasal augmentation. After the surgery, symptoms of epiphora had resolved and aesthetical improvement of facial deformities was also prominent. Management of old orbital fracture poses additional challenges due to the complications that have occurred over time. Loss of functionality may seem impractical to manage because no function can be pertained. Nevertheless, it is important to still perform surgical repair for aesthetic purposes due to the psychological effect on their daily lives.